Employee relations practices and performance of Public Universities in Mount Kenya Region - Wanderi, Miriam Wanjiku (Meru; Miriam Wanjiku Wanderi, 2023)
The performance of public universities in terms of offering quality education training and their ability to overcome the skills mismatch in the demand-driven global and national labor markets is a key indicator of the universities' ability to realize their position and potential in this competitive sector of technological transformation as well as becoming drivers of knowledge economy. For this to come to full realization there is need to institute employee relation practices which would enable these universities to attain their mission and this is fueled through instilling practices that support the human capital asset. Thus, when the employee-employer relationships are streamlined through active staff participation, involvement, and engagement and having defined structures recognizing employee critical importance at the workplace then there would be high productivity which would result to organizational performance. The objectives of this study were to establish how the various employee relations practices of employee voice, staff promotions, and employee engagement at public universities in the Mount Kenya region influenced their performance. The study adopted descriptive survey research design. The study locale was all public universities in Mount Kenya Region and the target population was 2984 employees drawn from both the teaching and non-teaching staff as well as human resource officers. The study adopted stratified random and purposive sampling procedures and the study derived a sample size of 271 employees. Data was gathered by use of a questionnaire which was subjected to pre-test to ensure its reliability and validity. Piloting of the questionnaire to check on its reliability was done from South Eastern Kenya University which was outside the sampled public universities in Mount Kenya region whose results were not included in the final research project results. All the questionnaires were termed as valid with 88.6% response rate. Cronbach$1 (Bs alpha was used as a test for reliability while normality test on all variables got a significant level of more than 0.05 which was a clear indication of normal distribution. The study used basic descriptive statistics such as frequencies and percentages because they could easily be interpreted. Inferential statistical analysis was also adopted to support the model. The study generated both qualitative and quantitative data which adopted the use of five-point likert scales, measures of central tendency, and use of multiple regressions analysis. The data was presented through the use of tables, charts, and figures. Correlation analysis was used in this study to depict the relationship between the independent variables and the dependent variable. Multiple regression model analysis was used to test the influence of employee voice, staff promotions and employee engagement to public universities performance. The study established a multiple correlation of 0.535 between the employee relation practices and organizational performance. The study drew a conclusion that employee relations practices of employee voice, staff promotions and employee engagement influenced their performance. The study recommended to the universities managements to employ employee voice as the best practice since it was the most significant. It also recommended the use of best promotions practices which were fair and equitable to all employees as this would reduce absenteeism levels, reduce employee turnover and improve overall productivity. The study recommended further areas of study like flexible working arrangements, reward and recognition, continuous training, work place health and safety and work-life balance other than those covered by this study. It also recommended for a similar study to be carried out in other universities outside Mount Kenya regions
A Research project submitted in partial fulfillment of the requirements for conferment of the degree of master of business administration in the Meru University of Science and Technology